2015
DOI: 10.1097/aln.0000000000000686
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Mean Arterial Pressure Variability and 30-day Mortality in Patients Having Noncardiac Surgery

Abstract: Although lower mean arterial pressure is strongly associated with mortality, lower intraoperative blood pressure variability per se is only mildly associated with postoperative mortality after noncardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
207
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(236 citation statements)
references
References 25 publications
8
207
0
5
Order By: Relevance
“…Three studies investigated the effect of IOH (presented as MAP absolute level) on postoperative 30‐day mortality, and IOH was defined as MAP < 60 mm Hg. An intra‐operative MAP < 60 mm Hg for 1‐5 minutes was not associated with postoperative 30‐day mortality [OR = 1.15, 95% CI (0.95, 1.4), I 2 = 0, Z = 1.43, P = .154], but an intra‐operative MAP < 60 mm Hg for more than 5 minutes was associated with an increased risk of postoperative 30‐day mortality [OR = 1.11, 95% CI (1.06, 1.17), I 2 = 51.9%, Z = 4.28, P < .0001].…”
Section: Resultsmentioning
confidence: 99%
“…Three studies investigated the effect of IOH (presented as MAP absolute level) on postoperative 30‐day mortality, and IOH was defined as MAP < 60 mm Hg. An intra‐operative MAP < 60 mm Hg for 1‐5 minutes was not associated with postoperative 30‐day mortality [OR = 1.15, 95% CI (0.95, 1.4), I 2 = 0, Z = 1.43, P = .154], but an intra‐operative MAP < 60 mm Hg for more than 5 minutes was associated with an increased risk of postoperative 30‐day mortality [OR = 1.11, 95% CI (1.06, 1.17), I 2 = 51.9%, Z = 4.28, P < .0001].…”
Section: Resultsmentioning
confidence: 99%
“…Il est possible que des durées cumulées d'hTPA soient interprétées comme un signal de danger à travers l'hypoxie tissulaire [19] mettant en jeu de multiples mécanismes compensateurs dont l'activation du système nerveux sympathique et la réaction inflammatoire avec des conséquences délétères. Les variations (hypo-et hypertension artérielle) de la pression artérielle, même relativement mineures, pourraient représenter des successions d'épisodes d'ischémie-reperfusion [2,20].…”
Section: Quels Sont Les Mécanismes Pouvant Expliquer L'association Enunclassified
“…The ABCD mnemonic is a useful aide memoire. However, contemporary studies have demonstrated that the presence of an ABC is not always sufficient to prevent end‐organ dysfunction, as among other clinical variables, hypotension, tachycardia and dysglycaemia are associated with poor outcome . This concept is also in line with the aviation checklist proposed by Jelacic et al., as they advocate the necessity of agreeing blood pressure and heart rate goals before commencement of anaesthesia .…”
mentioning
confidence: 92%